Controversy: Botulinum toxin in pregnancy - Paul Munish (Journal of Cutaneous and Aesthetic Surgery, 2009)
Botulinum toxin A (BTX-A), a purified protein derived from the bacteria Clostridium botulinum , has been widely used in aesthetic dermatology. Though BTX-A was initially used by neurologists extensively for neurological conditions such as blepharospasm, strabismus headaches, dystonia and spasticity, it has become popular among dermatologists and plastic surgeons for its cosmetic indications. Its use in pregnancy has been controversial and this article deals with the issues of use of BTX-A in pregnancy.